ORGANIZATION AND ACTIVITY OF THE POLICE BODIES IN THE BUKHARA PEOPLE'S SOVIET REPUBLIC - Zokirov Bobir Chorievich (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
This article addresses the issues of the organization and activities of the police agencies in the Bukhara People's Soviet Republic. The author highlights the shortcomings in the knowledge and skills of police officers, their lack of sufficient practical experience, and the existence of problems in material provision, which have led to cases of corruption and abuse of their service duties. Key attention is paid to issues related to law enforcement, including the judiciary, prosecution, public security, penalties, emir's courts, contracts, Red Army, crime prevention, prisons, detention centres, revolution, council, and Bolsheviks